Complications after different methods for fixation of mandibular angle fractures: network meta-analysis of randomized controlled trials. Issue 11 (November 2021) - Falci, S.G.M.; de Souza, G.M.; Fernandes, I.A.; Galvão, E.L.; Al-Moraissi, E.A.
Abstract: The aim of this review was to compare mandibular angle fracture fixation methods that were evaluated through randomized clinical trials considering postoperative complications. Additionally, different treatment methods were ranked based on their performance. A systematic review was performed based on the Cochrane and PRISMA guidelines. The quality of evidence and network meta-analysis were conducted using the GRADE tool and R software, respectively. Four databases were searched, and the papers were selected based on the PICOS strategy. A total of 3584 papers were found. After screening 15 papers were included. One plate placed on lateral border (tension zone) presented lower risk than one plate placed on superior border (tension zone) for infection [risk ratio (RR): 0.48, 95% confidence interval (CI): 0.33 to 0.71] and plate removal necessity (RR: 0.44, 95% CI: 0.28 to 0.69), with moderate quality of evidence. There were no significant differences among the mandibular angle fracture treatments for malocclusion and paraesthesia outcomes. In conclusion, one plate placed on the lateral border in the tension zone is the best choice regarding postoperative infection and plate removal necessity when fixing mandibular angle fractures. None of the tested fixation methods were associated with a significant risk of malocclusion and paraesthesia events.